Exercise-based injury prevention in football - Faude, O.; Rommers, N.; Rössler, R. (German Journal of Exercise and Sport Research, 2018)
Injuries—a major concern in a high-intensity contact sport like football—are associated with possible short- and long-term harmful consequences for the individual, the team and club as well as for the whole society. Consequently, there is need for effective injury prevention in football at all levels of play, in all age groups and in both genders. The present review summarizes the current scientific evidence focusing on exercise-based injury prevention and presenting promising prevention strategies in different football populations and settings. There is convincing evidence that multimodal exercise-based injury prevention programs (IPP) can reduce injury incidence by more than 30% in athletes of different age groups and in both genders. Although relevant effects have already been shown for short sessions, increased frequency and regular integration into normal practice may increase efficacy up to an injury reduction of 50%. Most programs last about 15min and can easily replace traditional warm-up programs. Furthermore, there is increasing evidence that IPP beneficially affect neuromuscular performance parameters and biomechanical movement characteristics, which are associated with injury risk. There remains, however, a major gap between research on the short-term efficacy and long-term intervention strategies. IPP should be implemented continuously and with high fidelity as training effects are transient. It is crucial that future studies report implementation components in detail in order to facilitate the replication of successful interventions.